Programs for Teaching Drawing in the 1890S - Mejía Echeverri, Silvana Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Sluys and Puoillot, translated and published authors in the Revista de Instrucción Pública de Colombia (Journal of public instruction of Colombia), may be considered exponents of two pedagogical currents of the late twentieth century. Sluys sets out his experimental position, where there would be a type of drawing typical of children allowing them to express their feelings and thoughts; whereas Puoillot advocates support in geometry and in manual work, in order to train the eye and the hand, as well as teach the construction of plane shapes to apply them in the manufacture of several objects. The teaching contents and methods are derived from the authors’ ways of substantiating their conceptions; as a faithful reflection not only of their way to understand drawing, children, the world they were living in, and their sense of futurity, but also of two different positions that were struggling to be legitimized at the time; struggles where discussions about how to teach art were involved.